Diversity and multiplicity in uncertain times: the category of “difficult knowledge” in the sensitive contexts of education and social research - Markowska-Manista, Urszula; Baranowski, Mariusz (Przegląd Krytyczny, 2024)
This article explores the category of “difficult knowledge” within the sensitive contexts of education and social research amidst contemporary global transformations. Uncertain times marked by humanitarian crises, wars, migration, and socio-economic shifts challenge the stability and security of societies. Difficult knowledge encompasses emotionally charged, complex topics integral to social, political, and educational spheres, compelling individuals and groups to confront uncomfortable truths and deconstruct human understanding. This concept, introduced by Britzman (1998), addresses the cognitive and emotional struggles in engaging with traumatic representations of historical and social events. The paper highlights the necessity for educators and researchers to navigate these challenges, fostering critical and reflective analyses while managing their psychological impacts. It underscores the dual role of researchers as both empathetic human beings and objective professionals, particularly in extreme field conditions. Additionally, it discusses the implications of conspiracy theories as a form of difficult knowledge, emphasizing the need for educational strategies that promote critical thinking and resilience. The article calls for greater attention to the sensitivities of the research process and the ethical responsibilities in studying and teaching difficult knowledge.